Seafloor Morphology and Bathymetric Data Quality Evaluation Around Panjang Island, Banten Bay - Steven Solikin; Sri Pujiyati; Dwi Yuni Wulandari; Tri Ariyah Hari Saputra; Umar Darlan; A-Liem; Ardella Insya Firmanti (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2026)
Gathering accurate bathymetric data in shallow coastal waters proves to be difficult due to the environmental issues and operational constraints, especially in a semi-enclosed water like Banten Bay. This research intends to examine the seafloor morphology, in addition to assessing the quality of hydrographic data acquired through the use of single-beam echosounder (Odom Echotrac CV100) around Panjang Island Waters. The main line and cross line surveys of the survey were carried out using RTK-GNSS positioning and tidal corrections using 30 day observations relative to mean sea level. The bathymetric data show a gradual depth transition from 8 m nearshore to more than 20 m offshore. Ridges and basins are evident in the data indicating spatial variability. According to the results of a data quality assessment based on the IHO S-44 standard, 94.07% of data belonged to Order 2, 76.67% to Order 1a/1b, 56.30% to Special Order and 38.52% to Exclusive Order with data errors below 7%. As the above results suggest, the general hydrographic mapping by the dataset is of reliable accuracy, which does not achieve highest accuracy consistently. The study’s main contribution is the demonstration of performance and practical limitations of single beam echosounder surveys in shallow water environment with a quantification of data quality compared to IHO standard. This study provides a validated methodology for low-cost bathymetric mapping of other similar semi-enclosed coastal water.